A comparative study between Staplers and Hand-Sewn Anastomosis in Gastrojejunostomy Surgery in Shaheed Suhrawardy Medical College Hospital - A S M Farhad Ul Hassan; S M Quamrul Akther; Akhter Ahmed; Mohammad Jayedul Islam; Rumana Ahmed; Sharmin Akter Suma; Maria Parveen; Mohammad Saifuddin Khan (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: Gastrointestinal anastomoses are common surgical procedure which is being done on different situations from many years back. In earlier days it was done by manual anastomotic technique using sutures. Day by day anastomotic techniques were developed and stapled devices are being used to make the anastomoses. In recent years most of the anastomoses in advanced countries have been done by staple devices and now it is also popular in our country. Very recently, advances in intestinal stapling devices have led to an increased frequency of stapled anastomoses for a variety of proposed beneficial reasons like better blood supply, reduced tissue manipulation, minimum tissue trauma and oedema, uniformity of sutures, wide lumen at the site of anastomosis than double layered suturing and the easy and rapidity of anastomosis. Considering the above advantages, stapled technique has now become good alternative method of anastomosis than hand-sewn technique in gastrointestinal surgery, specially in gastrojejunostomy operation. Aim:This study was designed to find out the outcome between stapling and hand-sewn gastrojejunostomy. Methods:This cross sectional, hospital based observational comparative study was carried out in the indoor of different surgical units of Shaheed Suhrawardy Medical College Hospital from September 2014 to March 2015, between two groups of patient who underwent gastrojejunostomy surgery. Total study populations were 100 which were divided into two groups. 50 anastomoses were done by stapled technique and other 50 patients anastomosis were done by hand-sewn technique. But in both groups there were two types of patients, in benign disease only gastrojejunostomy and malignant disease radical partial gastrectomy and gastrojejunostomy were done. The two groups were compared on various intra operative and postoperative outcomes. Results: In this study it was found that anastomotic integrity was better in stapled technique rather than hand-sewn anastomoses. Other variables like anastomotic time 16.96 minutes vs. 21.45 minutes, total operating time 115.2 minutes vs. 135.5 minutes, return of bowel sound 4.52 days vs. 5.1 days, postoperative hospital stays 12.28 days vs. 13.58 days and postoperative complications 14% vs. 34% in cases of stapled and hand-sewn anastomoses respectively. J Shaheed Suhrawardy Med Coll 2024; 16(2): 92-98